Räddningsinsatser och brandskydd i underjordsgruva : Rökspridningsberäkningar i Kiruna järnmalmsgruva och arbetsmetoder vid räddningsinsatser i underjordsgruvor - Johnsson, Linn; Kaj, Sara (2016)
Ten persons were in need of help after a fire started along the main road in Kiruna underground mine. They were located at different levels of the mine. The fire department’s capacity of handling underground fires was tested, but the rescue operation was still successful. An underground mine can consist of many and long drifts, and a fire underground differ from a fire in a building. Mainly it is the smoke and the reduced visibility that are the risks underground, and it is hard to predict the smoke spread.The purpose with this thesis is to combine the fire protection in an underground mine with a plausible rescue operation. This will be done by reviewing the relevance of the current regulations and evaluate the risks and possible measures. During the work five interviews have been performed and also four smoke spread simulations in LKAB:s mine in Kiruna where performed using the program Ventsim. Ventsim is a program that is used for simulating ventilation in a mine by building a virtual model of the drifts of the mine. The current fire protection in an underground mine primarily consists of rescue chambers, alarm, sprinkled areas, sectioning, education, handheld fire-extinguishers on all vehicles and possibly an internal fire rescue service. The majority of the fires in underground mines are fuel controlled, flashover are unlikely. A great part of the heat from the smoke is absorbed by the rock walls, the smoke is cooled, and mixes evenly over the cross section. The results showed that rescue operations in underground mines today are performed flexibly. A rescue operation demands a for example respiratory protection apparatus and personnel, and a guide is a valuable asset. Other risks during operations in underground mines are long access routes, a limited amount of air, smoke, communication, disorientation and spalling. For the simulations the heat release rates were assumed to be 1, 5, 15 and 30 MW to correspond to a heavy goods vehicle with incombustible load. The air velocity in the simulations was 2 m/s. ...